Challenges for planning climate change resilience through the co-creation living lab approach in the Mediterranean coastal town of Piran - Kumer, Peter; Meulenberg, Cécil; Kralj, Erik (Journal for Geography, 2022)
Climate change resilience for urban coastal communities is a pressing matter considering hazards like sea-level rise, coastal flooding and erosion. Adapting to such changes and creating climate change resilience should be an all-stakeholder process. This paper discusses the early stages of stakeholder participation through a co-creation living lab (LL) approach in the Mediterranean coastal town of Piran. To achieve climate change resilience ecosystem-based approaches (EBAs) are used as tools, while in Piran the novel coastal city LL (CCLL) approach is supposed to facilitate a process to achieve acceptance and implementation of such EBA solutions, through consented decision of representative stakeholders from each of the quadruple helix framework, including citizens. During this process several organisational limitations were encountered such as the question of incentivizing stakeholders, man-hour devotion, appointing contact persons within large organisations, and the challenge of organising continuous personal face-to-face meetings. Parallel to previous findings that defining a shared vision is necessary for a successful CCLL, we emphasize that newly retrieved specific challenges identified through personal communication with stakeholders, and capitalising on those, further motivated the stakeholders. These specific challenges represent pressing issues, for example: how to retrieve and revalorize the historical water management system; how to improve the existing early warning system; how to empower and educate, through climate action, the town’s community that is facing population decline through tourism gentrification. The experience by the authors of this paper suggests that continuous interaction with stakeholders and facilitating multidisciplinary activities based on stakeholder’s prior knowledge and experience, are best practices in the co-creation of the urban living lab. Funding This research has received funding from the European Union’s Horizon 2020 research and innovation program under grant agreement No. 101003534. Acknowledgments The authors would like to acknowledge and thank all the engaged stakeholders for their involvement and sharing their visions, as well as previously project-engaged colleagues at ZRS (She Mackenzie Hawke, Blaz Lenarcic, Irina Moira Cavaion and Kristjan Nemac), and the SCORE project partners for their input and guidance.